Designing 8-Bit multiplier - Yee, M.F (University Malaysia Sarawak, UNIMAS., 2006)
The Fundamental of Multiplying two binary Numbers is the most often use arithmetic operation in the Digital Signal Processor. Therefore, Multiplier design block is especially crucial in VLSI prospectus when Speed and Area is the concern. Many of the Design Topologies regarding this operation has been approached over the years.